ANALISIS KEBIASAAN BELAJAR PADA SISWA BERPRESTASI AKADEMIK DI SEKOLAH DASAR - Chaerunnisa Dinda Aulia; Fitri Siti Sundari; Rukmini Handayani (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
This research is a descriptive qualitative research. Sampling of data sources was carried out by purposive sampling. The purpose of the study was to analyze the study habits of students with academic achievement ranking one to three in elementary schools. The subjects of this study were students in grades one to three in grades II, III, IV, V and VI at SDN Parakan 01. The results of the analysis showed that the study habits of students with academic achievements ranked one to three had good study habits and differed among other students when the learning process took place at home or at home. at school. Academic achievement students have a regular study schedule, have an interest in reading textbooks or books of various knowledge, take notes on material lessons with structured and neat writing, use free time to complete assignments, concentrate while studying, have facilities that support learning, have space comfortable learning, have 2D or 3D learning media and information technology tools as a means of learning, have a variety of books such as theme books, history books and other knowledge books that are used to support learning, like quiet learning conditions and enjoy learning with other friends at school. his class. All good study habits in academically achieving students occur because of the guidance when doing learning carried out by teachers and parents.